Notching and Pulsatility Index of the Uterine Arteries and Preeclampsia in Twin Pregnancies - Springer, Stephanie (J Clin Med, 2020)
Increased uterine artery Doppler indices have been shown to be associated with preeclampsia and adverse pregnancy outcomes in singleton and twin pregnancies. At 20–22 weeks of gestation, we assessed the use of notching, the highest, lowest, and mean pulsatility index (PI), and the combination of notching and PI of the uterine arteries to screen for preeclampsia. This was done in a cohort of 380 twin pregnancies. The results showed that the combination of notching and the highest PI above the 95th centile of the uterine arteries gives the best screening characteristics for preeclampsia in twin pregnancies. We calculated sensitivities for preeclampsia for notching, highest PI, and the combination of notching and the highest PI of 50%, 45% and 91%, with specificities of 96%, 96% and 93%, respectively. The present findings demonstrate that notching, increased highest PI, and the combination of notching and the highest PI of the uterine arteries is associated with an increased risk of preeclampsia in twin pregnancies. We observed the highest sensitivity and specificity by using the combination of notching and the highest PI of the uterine arteries.